2017
DOI: 10.1111/sms.12939
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of acute groin injuries in the hip flexor muscles — a detailed MRI study in athletes

Abstract: Hip flexor injuries account for one-third of acute groin injuries; however, little is known about specific injury characteristics. The aims of this study were to describe acute hip flexor injuries using magnetic resonance imaging (MRI) in athletes with acute groin pain and to compare specific muscle injuries with reported injury situations. Male athletes with acute groin pain were prospectively and consecutively included during three sports seasons. MRI was performed within 7 days of injury using a standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
2
20
1
3
Order By: Relevance
“…Adductor longus is the most frequently injured muscle, and has three characteristic injury locations: proximal insertion, musculotendinous junction (MTJ) of the proximal tendon and MTJ of distal tendon 4. Proximal rectus femoris injuries often included injury to the tendon itself, predominantly the indirect tendon 5. Iliopsoas injuries can be divided into distinct iliacus and psoas injuries, with iliacus injuries being most frequent (92%), and predominantly occurred at the MTJ 5…”
Section: What Did I Find?mentioning
confidence: 99%
“…Adductor longus is the most frequently injured muscle, and has three characteristic injury locations: proximal insertion, musculotendinous junction (MTJ) of the proximal tendon and MTJ of distal tendon 4. Proximal rectus femoris injuries often included injury to the tendon itself, predominantly the indirect tendon 5. Iliopsoas injuries can be divided into distinct iliacus and psoas injuries, with iliacus injuries being most frequent (92%), and predominantly occurred at the MTJ 5…”
Section: What Did I Find?mentioning
confidence: 99%
“…Acute strains often occur at the musculotendinous junction, specifically of the adductor longus, rectus femoris, and iliopsoas muscles. 87,88 Acute adductor longus and rectus femoris injuries may also involve tendinous rupture/ avulsion, primarily at the proximal insertions (FIGURE 2). 87,88 In contrast to strains, groin overuse injuries more often involve bone and tendons and their insertions, and rarely involve the rectus femoris.…”
Section: Types Of Sports and Injuriesmentioning
confidence: 99%
“…87,88 Acute adductor longus and rectus femoris injuries may also involve tendinous rupture/ avulsion, primarily at the proximal insertions (FIGURE 2). 87,88 In contrast to strains, groin overuse injuries more often involve bone and tendons and their insertions, and rarely involve the rectus femoris. 34 Acute adductor muscle injuries usually occur during kicking and change of direction.…”
Section: Types Of Sports and Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The iliopsoas has been recently implicated in 25% of acute groin injuries . Other studies similarly indicated that iliopsoas disorders were found in 25% to 30% of athletes with acute groin injury and 12% to 36% of athletes with chronic groin pain . Common injury mechanisms involve kicking, sprinting, and changes of direction in sports such as soccer, basketball, and handball .…”
mentioning
confidence: 99%